2008
DOI: 10.1002/ccd.21814
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative angiographic methods for bifurcation lesions : A consensus statement from the European Bifurcation Group

Abstract: The treatment of bifurcation lesions is complex and increasingly common. A growing number of dedicated bifurcation devices are under clinical evaluation, but no standardized methodology exists. Specifically, the angiographic analysis of bifurcation lesions is not standardized and current QCA packages are not designed for bifurcation lesions. This consensus statement outlines the limitations of conventional QCA in the bifurcation application, and outlines a new standard approach for the analysis and reporting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 17 publications
0
59
0
Order By: Relevance
“…However, regarding conventional QCA for the MV in our study, it has been reported that the %DS of the MV is inversely correlated with the FFR value, whereas the %DS of the SB determined by conventional QCA was unreliable and not correlated with physiological ischemia assessed by FFR. 40 Fourth, no stent thromboses were seen in either the FKB or the no-FKB groups. This can potentially be explained by: (1) the low sample size used to detect stent thrombosis; (2) exclusion of complex lesions from the study population (ie, 2-stent strategy and long stenting); and (3) high use of IVUS.…”
Section: Study Limitationsmentioning
confidence: 84%
“…However, regarding conventional QCA for the MV in our study, it has been reported that the %DS of the MV is inversely correlated with the FFR value, whereas the %DS of the SB determined by conventional QCA was unreliable and not correlated with physiological ischemia assessed by FFR. 40 Fourth, no stent thromboses were seen in either the FKB or the no-FKB groups. This can potentially be explained by: (1) the low sample size used to detect stent thrombosis; (2) exclusion of complex lesions from the study population (ie, 2-stent strategy and long stenting); and (3) high use of IVUS.…”
Section: Study Limitationsmentioning
confidence: 84%
“…Bifurcation angle was defined as the angle between the distal MV and the SB at its origin using the angiographic projection with the widest separation of the two branches [5]. For quantitative coronary angiographic (QCA) analysis of a total of 8 segments, bifurcation lesions were divided into the proximal reference, MV proximal (proximal to SB take-off), MV middle (<5 mm distal to take-off), MV distal, MV distal reference, SB ostial (<5 mm distal to take-off), SB distal and SB reference segments (fig.…”
Section: Methodsmentioning
confidence: 99%
“…Post procedure after stenting was evaluated in the same projection. 15 Angiographic success was defined as the achievement of TIMI 3 flow with a residual stenosis b30% for the MV and b50% for the SB.…”
Section: Data Collection and Angiographic Analysismentioning
confidence: 99%